Microstructural Alterations in Bipolar and Major Depressive Disorders: A Diffusion Kurtosis Imaging Study. Issue 4 (23rd April 2020) - Sawamura, Daisuke; Narita, Hisashi; Hashimoto, Naoki; Nakagawa, Shin; Hamaguchi, Hiroyuki; Fujima, Noriyuki; Kudo, Kohsuke; Shirato, Hiroki; Tha, Khin K.
Abstract : Background: Identifying structural and functional abnormalities in bipolar (BD) and major depressive disorders (MDD) is important for understanding biological processes. Hypothesis: Diffusion kurtosis imaging (DKI) may be able to detect the brain's microstructural alterations in BD and MDD and any differences between the two. Study Type: Prospective. Subjects: In all, 16 BD patients, 19 MDD patients, and 20 age‐ and gender‐matched healthy volunteers. Field Strength/Sequence: DKI at 3.0T. Assessment: The major DKI indices of the brain were compared voxel‐by‐voxel among the three groups. Significantly different voxels were tested for correlation with clinical variables (ie, Young Mania Rating Scale [YMRS], 17‐item Hamilton Depression Rating Scale [17‐HDRS], Montgomery‐Åsberg Depression Rating Scale, total disease duration, duration of current episode, and the number of past manic/depressive episodes). The performance of the DKI indices in identifying microstructural alterations was estimated. Statistical Tests: One‐way analysis of variance (ANOVA) was used for group comparison of DKI indices. The performance of these indices in detecting microstructural alterations was determined by receiver operating characteristic (ROC) analysis. Pearson's product–moment correlation analyses were used to test the correlations of these indices with clinical variables. Results: DKI revealed widespread microstructural alterations across the brain in each disorder ( P < 0.05). Some were significantly different between the two disorders. Mean kurtosis (MK) in the gray matter of the right inferior parietal lobe was able to distinguish BD and MDD with an accuracy of 0.906. A strong correlation was revealed between MK in that region and YMRS in BD patients ( r = −0.641, corrected P = 0.042) or 17‐HDRS in MDD patients ( r = −0.613, corrected P = 0.030). There were also strong correlations between a few other DKI indices and disease duration ( r = −0.676 or 0.626, corrected P < 0.05). Data Conclusion: DKI detected microstructural brain alterations in BD and MDD. Its indices may be useful to distinguish the two disorders or to reflect disease severity and duration. Level of Evidence: 2 Technical Efficacy Stage: 3 J. Magn. Reson. Imaging 2020;52:1187–1196.